2006
DOI: 10.1038/sj.pcan.4500882
|View full text |Cite
|
Sign up to set email alerts
|

High-dose radiation employing external beam radiotherapy and high-dose rate brachytherapy with and without neoadjuvant androgen deprivation for prostate cancer patients with intermediate- and high-risk features

Abstract: The role of neoadjuvant androgen deprivation (NAD) in high-risk prostate cancer patients receiving high-dose radiotherapy (RT) remains unstudied. To evaluate the effect of a course of NAD, we reviewed the experiences of three institutions treating these patients with combined RT and high-dose rate brachytherapy (HDR). Of 1260 prostate cancer patients with high-risk features (pretreatment prostate-specific antigen (PSA) X10, Gleason Score (GS) X7, or T stage XT2b), 560 received no NAD (n ¼ 308) or NAD for p6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
0
13
1
5
Order By: Relevance
“…The median number of patients accrued per institution was 8 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and the average was 9 patients. The average monthly accrual for the study was 5.9 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median number of patients accrued per institution was 8 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and the average was 9 patients. The average monthly accrual for the study was 5.9 patients.…”
Section: Resultsmentioning
confidence: 99%
“…There have been multiple updates of their results. (8,(14)(15)(16)(17)(18) They have continued to dose escalate using increasingly larger fractions of HDR treatment ranging from 5.5-6.5 Gy × 3 to 8.25-11.5 Gy × 2 combined with 46 Gy of external beam radiotherapy. The most recent update showed the treatment is well tolerated with favorable biochemical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…8,[13][14][15]19 It was our choice to treat the boost before EBRT for the following reasons; first at the start of SBRT, patients were naive from acute toxicities linked to EBRT; second at the start of the EBRT, prostate cancer cells were exposed at high radiation dose (BED2 109.25 Gy). Up to date, there is no larger studies on HDR-like prostate cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Until now, hypofractionation with high dose rate has been utilized by high dose rate brachytherapy (HDR-BRT), establishing itself as a viable and safe approach as monotherapy or boost after EBRT. [8][9][10][11][12][13][14][15] The HDR-BRT has the advantage of better accuracy to the dose delivered and avoidance of complications secondary to organ movement compared to EBRT. In intermediate-and high-risk disease, HDR-BRT alone may not deliver adequate dose to periprostatic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…There were too few high-risk patients treated without ADT (n = 2) to do a meaningful comparison of outcomes without vs. with ADT (Figure-2). Vargas et al (27) observed worse DMFS, prostate-cancer specific survival, and OS in patients with a Gleason score 8-10, palpable disease, and a PSA ≥15 ng/mL who received ADT. It is possible that patients who received ADT may have had a history of congestive heart failure or myocardial infarction, accounting for the poor outcomes with ADT in that report (28).…”
Section: Medianmentioning
confidence: 99%